Frequency of Osteoporosis in Iatrogenic Cushing’s syndrome: Scenario of outpatient department in urban hospitals (Bangladesh Journal of Medicine, 2020)
Background: Cushing’s syndrome is caused by excessive activation of glucocorticoid receptor. Iatrogenic Cushing syndrome is the prevalent one world -wide .Patients with Cushing’s syndrome has a high prevalence of osteoporosis.Objective: To see the prevalence of osteoporosis in Iatrogenic Cushing’s syndrome patient.Method: This descriptive cross-sectional study included 211 diagnosed case of Cushing’s syndrome during the time period of December 2013 to December 2018 in outpatient department of Dhaka Medical College and Health and Hope Hospital. Final diagnosis was done on the basis of clinical feature, serum basal cortical level and BMD. We found male were prevalent one (56%).80.56% showed biochemical evidence of Cushing’s syndrome. BMD was done in 113 patients compared with a reference population by means of T score, 17.69% patient in osteoporotic range.Conclusion: The prevalence of osteoporosis and osteopenia is age and sex independent. Judicial use of steroid and co administration with calcium, bisphosphonate can prevent osteoporosis. Treatment with bisphosphonates should be considered in all patients (irrespective of age) with Cushing’s syndrome with a low BMD to reduce fracture.Bangladesh J Medicine Jan 2020; 31(1) : 18-21